The Impact of Social Media Campaign on Green Coffee Image at Instagram @BLACKPASSION.ID - Aditya Eka Putra; Lian Agustina Setiyaningsih; Fitria Setyaningrum; Sri Widayati (Unitri Press, 2022)
In recent years, the research on social media especially Instagram becomes gradually popular along with the upsurge of the developing number of users. This is an opportunity for companies to use social media as a campaign tool, specifically to build the image of a product through campaigns on social media. In this research, an evaluation of the impact of social media campaigns on the green coffee image is conducted on Instagram @blackpassion.id. In the study, researchers use a quantitative approach as a research methodology. There are two variables used in this study, the independent variable